Sales tax compliance behavior among small and medium manufacturers in Malaysia - Tee, Leap Sing (2021)
Tax compliance behaviour has been addressed as a continuous serious concern globally. However, empirical research on sales tax compliance in Malaysia is still scarce. The present study can be considered as a first attempt that was conducted in the context of sales tax version 2.0 for sales tax compliance among manufacturers in Malaysia. The main objective of this study was to investigate the determinant of sales tax compliance behaviour among small and medium manufacturers who are required to be registered. Sales tax is a single-stage tax imposed on taxable goods manufactured locally and sold by a registered manufacturer, as well as on taxable goods imported into Malaysia. Fischer model was used with a consideration on the relationships of socio-psychological factors (tax complexity, peer influence, tax fairness, tax knowledge, service quality and compliance cost), and economic factors (tax complexity), with sales tax compliance. As a new contribution to tax compliance knowledge, the relationship between tax compliance behaviour and its determinants was also examined. The population consisted of respondents who were working in SME manufacturing. All the items in the study’s variables were assessed using the 5-point Likert scale. Multiple regression analysis was employed to test the hypotheses. The findings showed that peer influence and tax knowledge had significant influences on compliance behavior. Meanwhile tax complexity, tax fairness, tax law and enforcement, service quality and compliance cost variable on tax compliance were non-significant. This study concluded with the theoretical and practical implications for the tax authority and the government of Malaysia. This study has significant inputs to the government, tax agencies and public economic policy makers by providing empirical insights into factors affecting sales tax compliance behaviour among the Malaysian SMEs taxpayers, as well as valuable information to SMEs owner-managers in order to increase their compliance in the future. The information is crucial in order to formulate social, economic and political policies, as well as to enable the government to be more realistic in designing strategies and policies on tax compliance behaviour in Malaysia.